Development of Non-Proprietary Ultra-High-Performance Concrete Mix Designs - McDaniel, Amy (My University, 2017)
Ultra-High-Performance Concrete (UHPC) is defined by the Federal Highway Administration (FHWA) as having a compressive strength of 21.7 ksi (kilo-pounds per square inch), a post-cracking tensile strength 0.72 ksi, and high flowability. This product is desired by the Oklahoma Department of Transportation (ODOT) to construct durable deck joints, both for repair and use on new bridges. However, commercial UHPC is prohibitively expensive. This study sought to develop a cost-effective, non-proprietary mix design for UHPC using materials accessible in the State of Oklahoma. Mix designs were iterated from the baseline of non-proprietary mix designs formulated for other regions of the U.S. The concept of particle packing, which seeks to optimize the combination of constituent gradations in order to minimize empty air space, was also employed to develop a mix with the properties of UHPC. Nine iterative groups, Series A through Series J, sought to produce the optimal combination of SCMs, the aggregate/cementitious material ratio, the water/cementitious material ratio, and the dosage of high-range water reducer. The three mixes strongest in compression were selected to add fiber reinforcement and study the effect of heat curing. Properties key to its use on bridge joints, including bending and elasticity, were tested. While this study did not produce a mix design meeting the FHWA definition of UHPC, a cost-effective non-proprietary mix design was established that has high mortar flow, a first-cracking tensile strength of 2.0 ksi, and a compressive strength exceeding 20 ksi at 3 days with heat curing. Additionally, field replicable mixing, placing, and curing procedures were developed for use in repairing bridge joints and future applications.
Keywords: ultra-high-performance concrete, mix design, particle packing